Defects in complex oxide thin films for electronics and energy applications: challenges and opportunities. Issue 11 (27th July 2020) - Li, Weiwei; Shi, Jueli; Zhang, Kelvin H. L.; MacManus-Driscoll, Judith L.
Abstract : This review focuses on recent progress in defect-engineered novel functionalities of complex oxide thin films for electronics and energy applications, and current challenges and perspectives. Abstract : Complex transition-metal oxides (TMOs) are critical materials for cutting-edge electronics and energy-related technologies, on the basis of their intriguing properties including ferroelectricity, magnetism, superconductivity, (photo- and electro-) catalytic activity, ionic conductivity, etc. These properties are fundamentally determined by the partially occupied TM d orbitals and the corresponding local coordination environments, which are sensitive to defects (or impurities), compositions, grain boundaries, surface and interfaces, etc. Recently, motivated by the advance in thin film epitaxy techniques, the complex oxide research community has shown great interest in controlling defects for enhanced or even unprecedented functional properties. In this review, we provide an overview on recent progress in tuning the functional properties of TMO thin films via defect engineering. We begin with a brief introduction to the defect chemistry of TMOs, including types of defects and their effects on local atomic structure, electron configurations and electronic structure, etc. We then review recent research efforts in engineering defects in TMOs for novel functionalities, such as ferroelectricity, magnetism, multi-ferroelectricity and dielectricity, two-dimensional electron/hole gas, metal–insulator transitions, resistive switching, ionic conductivity, photo-electrocatalysis, etc. We also provide insights into understanding the defect-structure–property relationship from the perspective of electronic structure. Finally, challenges and perspectives on control of defects for design of novel devices are discussed.